2017
DOI: 10.1111/raq.12223
|View full text |Cite
|
Sign up to set email alerts
|

Physiological roles of tryptophan in teleosts: current knowledge and perspectives for future studies

Abstract: Tryptophan is an essential amino acid with a huge functional versatility, in addition to its participation in protein synthesis. Because of the complexity of its metabolism, and the functional relevance of several of its metabolites, it directly or indirectly participates in a wide array of physiological pathways. This amino acid is a precursor for the synthesis of the neurotransmitter/neuromodulator serotonin (5HT), the hormone melatonin and kynurenine and related compounds such as kynurenic acid, quinolinic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
96
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(98 citation statements)
references
References 211 publications
(432 reference statements)
2
96
0
Order By: Relevance
“…Similar to present results, Taheri Mirghaed et al () reported that high stocking density significantly increased oxidative stress characterized by MDA elevation. Trp has antioxidant ability by direct reaction with pro‐oxidant molecules and/or stimulation of the antioxidant enzymes (Hoseini et al, ). The present results showed that 5 g Trp per kg diet potentiated to suppress oxidative stress both under the LD and HD conditions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to present results, Taheri Mirghaed et al () reported that high stocking density significantly increased oxidative stress characterized by MDA elevation. Trp has antioxidant ability by direct reaction with pro‐oxidant molecules and/or stimulation of the antioxidant enzymes (Hoseini et al, ). The present results showed that 5 g Trp per kg diet potentiated to suppress oxidative stress both under the LD and HD conditions.…”
Section: Discussionmentioning
confidence: 99%
“…The present results showed Trp at 5 g per kg diet significantly improved the fish immune strength, but 10 g Trp per kg diet significantly suppressed the immune strength of the fish. Immunomodulatory effects of Trp have been assessed in several studies; however, the results have been variable and contradictory [reviewed by Hoseini et al (2019b)]. Several studies have shown Trp administration significantly mitigated immunosuppression caused by chronic thermal (Akhtar, Pal, Sahu, & Ciji, 2013b;Akhtar et al, 2013a;Kumar et al, 2018), osmotic (Akhtar et al, 2013b(Akhtar et al, , 2013a and pollution (Ciji, Sahu, Pal, & Akhtar, 2015) stresses in different species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Threonine contributes to bone formation, fat metabolism and digestive function; controls the body's health and immune system, liver and nerves and maintains body protein (Qaisrani et al, 2018). Tryptophan, as reported by Iwuji et al (2014) and Hoseini et al (2019), triggers the production of serotonin, stimulates niacin production, increases appetite and feed efficiency, stimulates growth, and increases body weight. The production of meat and eggs in the grower, pullet and layer phases is largely determined by growth in the starter phase.…”
Section: Introductionmentioning
confidence: 95%
“…For chicken, threonine and tryptophan are the third critical amino acids after methionine and lysine (Qaisrani et al, 2018). Threonine affects feed intake and body weight (Estalkhzir et al 2013), while tryptophan contributes to protein biosynthesis, builds muscle mass and stimulates immune responses, enhances the immune system, maintains internal proteins, induces growth and increases antibodies, and acts as serotonin precursors and control aggressiveness (Younis et al, 2016;Hoseini et al, 2019). Supplementation of 0.23 -0.31% tryptophan in feed was reported to increase broilers' weight (Opoola, 2017).…”
Section: Body Weightmentioning
confidence: 99%